Perishable food cargo losses and damage in cold chains – an empirical analysis - Klopott, Magdalena (Straty i szkody w ładunkach żywności szybko psującej się w łańcuchach chłodniczych – analiza empiryczna, 2019)
The purpose of the paper is to investigate the main causes and factors of losses of or damage to perishable food cargo in the cold chain. The empirical analysis is based on a study of 1816 claims and survey cases conducted by a leading surveyor company in the period 2015-2018. The prevailing causes were divided into five categories: 1) breaking cold chain integrity; 2) unsuitability of packaging, stacking and preparation of cargo for transit (especially the lack of or insufficient pre-freezing or pre-cooling to the required carrying temperature); 3) delays in delivery; 4) errors and omissions in transport documents or shipment instructions; 5) administrative decisions. A closer examination of the results showed that human error was the root cause of many incidents, being responsible for approximately 50% of all examined claims. This points to the need to raise awareness among all cold chain stakeholders with regard to the specific requirements of perishable food cargo, pointing out in particular that even their minor breach may result in total loss or damage
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 6, s. 159-170
Keywords: cold chain; perishable cargo; cargo losses and damage; breaking cold chain integrity; food losses; łańcuch chłodniczy; ładunek szybko psujący się; straty i szkody ładunkowe; przerwanie ciągłości łancucha chłodniczego; straty żywności